Novel 61-bp Indel of RIN2 Is Associated With Fat and Hatching Weight Traits in Chickens - Lin, Wujian; Ren, Tuanhui; Li, Wangyu; Liu, Manqing; He, Danlin; Liang, Shaodong; Luo, Wen; Zhang, Xiquan (Frontiers in Genetics, 2021)
Ras and Rab interactor 2 (RIN2) gene, encoding RAS and Rab interacting protein 2, can interact with GTP-bound Rab5 and participate in early endocytosis. This study found a 61-bp insertion/deletion (indel) in the RIN2 intron region. The genotype analysis of mutation sites was performed on 618 individuals from 8 different chicken breeds, and it was found that the indel exists in each breed and the yellow feather chickens are mainly DD genotypes. Correlation analysis of growth traits and carcass traits of the F2 population of Xinghua and White Recessive Rock chicken, showed that the RIN2 61-bp deletion mutation site was significantly correlated with abdominal fat weight, abdominal fat rate, fat width and hatching weight traits (P < 0.05). RIN2 mRNA was expressed in all test tissues, and the expression level of abdominal fat was higher than that in other tissues. In addition, it was further found that the expression level of genotype DD RIN2 in abdominal fat was significantly higher than that of genotype II (P < 0.05). Transcription activity results showed that the luciferase activity of pGL3-DD vector was significantly higher than that of pGL3-II vector (P < 0.01). When knocking out the transcriptional binding sites of GATA-1 or GCN4, the transcriptional activity was significantly higher than that of pGL3-II (P < 0.01). The results showed the mutation was closely related to the abdominal fat-related and hatching weight traits of chickens, which may have reference value for molecular marker-assisted selection of chickens.